A vehicle-track-tunnel-soil model for evaluating the dynamic response of a double-line metro tunnel in a poroelastic half-space. (September 2018) - Di, Honggui; Zhou, Shunhua; Luo, Zhe; He, Chao; Xiao, Junhua; Li, Xue
Abstract: In this study, a three-dimensional vehicle-track-tunnel-soil model for evaluating the dynamic response of a double-line metro tunnel in a poroelastic half-space is developed. The model development consists of two steps. In the first step, the vehicle-track-tunnel-soil model in a full-space is developed. In the second step, based on the full-space model, the dynamic response of the poroelastic half-space is solved by using the 2.5-dimensional boundary integral equation and the Green's function. The developed vehicle-track-tunnel-soil model is validated against existing tunnel models and is demonstrated through a case study of the dynamic response induced by one-way and two-way train loads.